콩 유전자원의 지방함량과 지방산조성 평가 및 유용자원의 선발 - 송항림(Hang-Lin Song); 장은규(Eun Kyu Jang); 손은호(Eun Ho Son); 이구환(Ku Hwan Lee); 황세구(Se Gu Hwang); 윤건식(Geon Sig Yun); 이정동(Jeong-Dong Lee); 김홍식(Hong Sig Kim) (Korean journal of breeding, 2015)
한국자원 128개와 중국자원 214개 및 미국자원 37개를 포함한 총 379개의 국내외 콩 유전자원에 대한 지방 함량과 지방산 조성을 평가하고 유용자원을 선발하여 고품질 콩 품종 개발의 기초자료로 활용코자 수행되었다. 한국자원과 중국자원은 농촌진흥청 농업유전자원센터로부터, 미국자원은 경북대학교 식물유전육종연구실로부터 분양 받았다. 콩 유전자원의 지방함량은 평균 19.1%이었고, 12.7∼26.0%의 범위이었고, 포화지방산인 palmitic acid의 함량은 평균 10.6%이었고 범위는 4.1∼18.1%, stearic acid의 함량은 평균 2.9%이었고 범위는 1.9∼12.7%이었다. 불포화지방산인 oleic acid의 함량은 평균 28.2%이었고 범위는 15.3∼56%, linoleic acid의 함량은 평균 51.2%이었고 범위는 24.4∼68%, linolenic acid의 함량은 평균 7.1%이었고 범위는 3.4∼11.1%이었다. linoleic (ω-6)/linolenic(ω-3) acid 함량의 비율은 평균 7.5이었고 범위는 3.8∼17이었다. 포화지방산이 평균 13.5%이었고 범위는 6.7∼21.7%, 그리고 불포화지방산의 함량은 평균 86.5%이었고, 범위는 78.3∼93.4%이었다. 고지방품종 개발을 위한 지방함량이 25%이상인 고지방함량 자원으로는 중국자원인 Suinong 14, Dongnong 434 및 Dongnong 46의 3개이었다. Oleic acid 함량이 50%이상인 고 oleic acid함량 자원으로는 미국자원인 KLG12073과 KLG12074, 중국자원인 Jilin 14 및 한국자원인 Kwangan과 Bongeui의 5개이었고, linoleic acid의 함량이 60%이상인 고 linoleic acid 함량 자원으로는 미국자원 KLG12083과 KLG12081을 포함한 8개이었다. Linolenic acid의 함량이 4%이하인 저 linolenic acid 함량 자원으로는 미국자원 KLG12093와 KLG12096을 포함한 7개이었다. Linoleic acid(ω-6)/linolenic acid(ω-3)의 비율이 4.5이하로 낮은 자원은 미국자원 KLG12074 (3.8)와 KLG12073 (3.8), 한국자원 Kwangan (3.8)와 Bongeui (4.5) 및 중국자원 Dongnong 47 (4.3)의 5개이었다. This study was carried out to evaluate the oil contents and fatty acid compositions of 379 soybean germplasm accessions which is composed of 128 Korean, 214 Chinese and 37 USA accessions, and to select useful resources for the development of high oil content and quality fatty acid varieties in soybean. Korean and Chinese germplasm accessions were obtained from the National Agrobiodiversity Center, National Academy of Agricultural Science, Rural Development Administration, and USA accessions from the Plant Genetics and Breeding Laboratory of Kyungpook National University, Korea. The oil content ranges from 12.7∼26.0% with an average of 19.1% among accessions. The average contents and ranges of palmitic and stearic acid, saturated fatty acids (SFA), were 10.6% with a range of 4.1∼18.1% and 2.9% with a range of 1.9∼12.7% respectively, while those of oleic, linoleic and linolenic acid, unsaturated fatty acids (USFA), were 28.2% with a range of 15.3∼56%, 51.2% with a range of 24.4∼68% and 7.1% with a range of 3.4∼11.1% respectively. The average linoleic(ω-6)/linolenic(ω-3) acid ratio was 7.5 ranging from 3.8∼17, and the average SFA and USFA contents were 13.5% ranging from 6.7∼21.7% and 86.5% ranging 78.3∼93.4% respectively. Accessions with better essential properties were selected as useful resources for the development of high oil content and quality fatty acid varieties. Three accessions, Suinong 14, Dongnong 434 and Dongnong 46 from China contain oil higher than 25.0%, while five accessions including KLG 12073 and KLG 12074 from USA, Jilin 14 from China, Kwangan and Bongeui from Korea contain oleic acid higher than 50%. Eight accessions including KLG12083 and KLG12081 from USA contain linoleic acid higher than 60%. Seven accessions including KLG 12093 and KLG12096 from USA contain linolenic acid lower than 4%. Five accessions, KLG12074 and KLG12073 from USA, Kwangan and Bongeui from Korea, and Dongnong 47 from China were low linoleic acid(ω-6)/linolenic(ω-3) ratio resources with lower than 4.5.